2018
DOI: 10.3892/mmr.2018.8823
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone regulates endometrial stromal cell apoptosis and migration via the promotion of mitochondrial fission by activation of the JNK/Drp1 pathway

Abstract: Increased endometrial stromal cell (ESC) survival and migration is responsible for the development and progression of endometriosis. However, little is known about the mechanisms underlying ESC survival and migration, and limited therapeutic strategies that are able to reverse these abnormalities are available. The present study investigated the effects of zearalenone (ZEA) on ESC survival and migration, particularly focusing on mitochondrial fission and the c‑Jun N‑terminal kinase (JNK)/dynamin‑related protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 69 publications
5
24
0
1
Order By: Relevance
“…Increasing evidence indicates that mitochondrial fission promotes the initiation of mitochondrial apoptosis . Our transmission electron microscopy assay revealed that mitochondria presented as elongated filamentous structures in control cells, but exhibited small and punctate mitochondria in IR‐783‐treated cells (Figure A).…”
Section: Resultsmentioning
confidence: 78%
“…Increasing evidence indicates that mitochondrial fission promotes the initiation of mitochondrial apoptosis . Our transmission electron microscopy assay revealed that mitochondria presented as elongated filamentous structures in control cells, but exhibited small and punctate mitochondria in IR‐783‐treated cells (Figure A).…”
Section: Resultsmentioning
confidence: 78%
“…DRP1 phosphorylations are modulated by the ERK1/2, PKA and JNK signal pathways [26,27,28,29,30]. Furthermore, CDDO-Me influences ERK1/2 [20,31] and JNK phosphorylations [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…DRP1-S616 phosphorylation is regulated by the ERK1/2 and JNK signal pathways, which facilitate mitochondrial fission [27,29,30]. However, DRP1-S637 phosphorylation by PKA leads to detached DRP1 from mitochondria, thus inhibiting mitochondrial fission [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…In acute myocardial ischemia reperfusion injury and chronic heart fibrosis, activated JNK promotes mitochondrial fragmentation and cardiomyocyte death. Similarly, in liver cancer, rectal cancer, gastric cancer,49 endometriosis58 and cervical cancer,59 the JNK pathway has been identified as the upstream factor for mitochondrial fragmentation activation. In agreement with previous studies, we also found that inhibition of the JNK pathway repressed Drp1 expression and attenuated mitochondrial fragmentation.…”
Section: Discussionmentioning
confidence: 99%